Karakteristik Dan Penggunaan Obat Pasien Dispepsia Rawat Inap Di Rumah Sakit - Maura Zettira Shabrina; Nurmainah Nurmainah; Mohammad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
The 2006 Indonesian health data profile states that dyspepsia ranks 10th out of the top 10 most hospitalized diseases in all Indonesian hospitals with 34,029 cases (1.52%). This study aims to describe the characteristics of inpatient dyspepsia patients, determine the presentation of dyspepsia drug use, and describe comorbidities in inpatient dyspepsia patients at RSUD dr. Rubini Kabupaten Mempawah. The sampling method used purposive sampling and data were taken from medical records with a total of 110 patients. Data collection used medical record for inpatient dyspepsia patients at dr. Rubini Hospital, Mempawah Regency for the January-December 2020 period. The results in this study were dyspepsia patients who were hospitalized at dr.Rubini Hospital, Mempawah Regency, the dominant gender was female (74.55%), patients with the majority age ranged 46-55 years (23.63%), housewife work (52.72%) with a senior high school education (42.37%). Dyspepsia patients with marital status (77.28%), patients with the majority of non-smoking habits (82.73%), and patients with 3 days of hospitalization (27.27%). The most widely used drug use in RSUD dr. Rubini, Mempawah Regency, namely omeprazole injection (26.90%) and the most common combination treatment for dyspepsia is PPI + Cytoprotective + Antiemetic (49.10%). The most dominant comorbidities in inpatient dyspepsia patients at RSUD dr. Rubini, Mempawah Regency are hypertension and vertigo.